Voices from the world of Samuel Pepys - Bastable, Jonathan (David & Charles, 2007)
Provides accounts of various aspects of contemporary life, from the arts and entertainment, to politics and religion. This book captures the spirit of Restoration London, as it grew to become a major centre of international commerce and culture.